The Metabolism of Clostridium ljungdahlii in Phosphotransacetylase Negative Strains and Development of an Ethanologenic Strain - Lo, Jonathan; Humphreys, Jonathan R.; Jack, Joshua; Urban, Chris; Magnusson, Lauren; Xiong, Wei; Gu, Yang; Ren, Zhiyong Jason; Maness, Pin-Ching (Frontiers in Bioengineering and Biotechnology, 2020)
The sustainable production of chemicals from nonpetrochemical sources is one of the greatest challenges of our time. CO2 release from industrial activity is not environmentally friendly yet provides an inexpensive feedstock for chemical production. One means of addressing this problem is using acetogenic bacteria to produce chemicals from CO2, waste streams, or renewable resources. Acetogens are attractive hosts for chemical production for many reasons: they can utilize a variety of feedstocks that are renewable or currently waste streams, can capture waste carbon sources and covert them to products, and can produce a variety of chemicals with greater carbon efficiency over traditional fermentation technologies. Here we investigated the metabolism of Clostridium ljungdahlii, a model acetogen, to probe carbon and electron partitioning and understand what mechanisms drive product formation in this organism. We utilized CRISPR/Cas9 and an inducible riboswitch to target enzymes involved in fermentation product formation. We focused on the genes encoding phosphotransacetylase (pta), aldehyde ferredoxin oxidoreductases (aor1 and aor2), and bifunctional alcohol/aldehyde dehydrogenases (adhE1 and adhE2) and performed growth studies under a variety of conditions to probe the role of those enzymes in the metabolism. Finally, we demonstrated a switch from acetogenic to ethanologenic metabolism by these manipulations, providing an engineered bacterium with greater application potential in biorefinery industry.